2015
DOI: 10.1093/gerona/glv217
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Development of Autonomic Dysfunction in Heart Failure: Effects of Age in an Ovine Rapid-pacing Model

Abstract: Heart failure (HF) is predominantly a disease of older adults and characterized by extensive sympatho-vagal imbalance leading to impaired reflex control of heart rate (HR). However, whether aging influences the development or extent of the autonomic imbalance in HF remains unclear. To address this, we used an ovine model of aging with tachypacing-induced HF to determine whether aging affects the chronotropic and inotropic responses to autonomic stimulation and reduction in heart rate variability (HRV) in HF. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 39 publications
4
15
0
Order By: Relevance
“…We next sought to determine if the increase in symptom-free survival following tadalafil treatment was associated with any changes in cardiac contractility or cardiac dimensions. In line with our previous findings 1, [33][34][35] left ventricular dilatation and free wall thinning were observed following tachypacing ( Figure 1B & C). Tadalafil treatment did not reverse left ventricular dilatation but did normalize diastolic wall thickness from its nadir value observed one week after commencement of tadalafil treatment.…”
Section: Pde5 Inhibition Improves Symptom-free Survival and Enhances supporting
confidence: 93%
“…We next sought to determine if the increase in symptom-free survival following tadalafil treatment was associated with any changes in cardiac contractility or cardiac dimensions. In line with our previous findings 1, [33][34][35] left ventricular dilatation and free wall thinning were observed following tachypacing ( Figure 1B & C). Tadalafil treatment did not reverse left ventricular dilatation but did normalize diastolic wall thickness from its nadir value observed one week after commencement of tadalafil treatment.…”
Section: Pde5 Inhibition Improves Symptom-free Survival and Enhances supporting
confidence: 93%
“…Decreased heart rate variability in old sheep (Horn et al . ) suggests that an age‐associated increase in sympathetic tone is preserved across species. Sympathetic tone, activating β‐adrenoceptors, probably exacerbates the age‐associated increase in SR Ca content (Briston et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a separate group of animals, we have previously shown that, although the heart rate increases with age, spontaneous AF or left ventricular hypertrophy do not occur (Horn et al . , )…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations